Structural and photoluminescence properties of Cr3+ doped LaVO4 phosphor - Rai E.; Yadav R.S.; Kumar D.; Singh A.K.; Fulari V.J.; Rai S.B. (My University, 2025)
In this work, we have studied the structural and photoluminescence properties of Cr3+ doped LaVO4 phosphor prepared by solid state reaction method. The XRD patterns of phosphors give an idea about the unit cell volume, crystallite size and crystalline nature. The SEM images provide the morphological features of the phosphor samples. The unit cell volume and the particles size of the Cr3+ doped LaVO4 phosphors decrease on increasing concentration of Cr3+ ion. The elements present in the Cr3+ doped phosphors have been analyzed using EDS and color mapping techniques. The FTIR spectra of Cr3+ doped LaVO4 phosphors specify the vibrational bands present in the samples. The UV–vis absorption and PL excitation spectra of the phosphor samples give information about the excitation wavelengths. The optical band gap of LaVO4 phosphor is 3.56 eV, which decreases on increasing concentration of Cr3+ ion. The Cr3+ doped LaVO4 phosphor gives yellow (581 nm), red (634 nm) and NIR (700 and 765 nm) emissions upon 428 and 467 nm excitations, respectively. The lifetime of Cr3+ doped LaVO4 phosphor decreases on increasing concentration of Cr3+ ion. The Cr3+ doped phosphor also shows heat generation capacity upon 980 nm excitation. Therefore, the Cr3+ doped LaVO4 phosphor may be used for solid state lighting, NIR sources and heat generating devices. © 2022 Elsevier Masson SAS